PENGARUH EFFECTIVE TAX RATE, TUNNELING INCENTIVE, EXCHANGE RATE DAN MEKANISME BONUS PADA KEPUTUSAN TRANSFER PRICING PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang terdaftar pada Bursa Efek Indonesia Periode 2015-2019) - Nurul Baiti; Suryani Suryani (Jurnal Akuntansi dan Keuangan, 2020)
This study aims to determine the effect of Effective Tax Rate, tunnelling Incentive, Exchange Rate and Bonus Mechanism on Transfer Pricing decisions in companies. In this study Transfer Pricing is measured by the presence or absence of sales to special parties. The population in this study are Manufacturing Companies listed on the Indonesia Stock Exchange 2015-2019 which were 17 companies. This research uses the purpose sampling method. The analysis technique used is logistic regression analysis. The results of his research indicate that tunnelling Incentive negatively affects the transfer pricing decision and the effective tax rate, exchange rate, bonus mechanism does not affect the transfer pricing decision